Experimental Characterization of Electrostatic MEMS Resonators for Sensing Applications - Alattar, Basil Yousef Ahmad (2023)
A Master of Science thesis in Mechatronics Engineering by Basil Yousef Ahmad Alattar entitled, “Experimental Characterization of Electrostatic MEMS Resonators for Sensing Applications”, submitted in April 2023. Thesis advisor is Dr. Mehdi Ghommem. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).